خلق القيمة في ظل المقاربة الإدراكية للحوكمة و إمكانية تطبيقها على المؤسسات الدينية - غضبان, حسام الدين; روينة, عبد السميع (جامعة الوادي - University of Eloued, 2019)
بالرغم من التبني الواسع للمقاربة التشاركية للحوكمة و سيطرتها على المقاربة المالية " المبنية على مصالح المساهمين" إلا أن البراديغم الانضباطي الذي ميز كلاهما ممثلا في النظريات التعاقدية (نظرية الوكالة – نظرية حقوق الملكية – نظرية تكاليف التعاقدات( تجاهل الديناميكية الإنتاجية الفكرية في المؤسسة ،و هو ما عجل بظهور براديغم آخر بهدف إلى بناء تصور مغاير للكفاءة التنظيمية و الإدارية يهدف إلى كسر الجمود المعرفي بالمؤسسات عرف بــ " المقاربة الإدراكية للحوكمة" أو " الحوكمة الإدراكية"، والتي ترتكز على خلق القيمة من خلال تشجيع المهارات، التعلم، و الإبداع خاصة في ظل اقتصاد المعرفة أين ينظر للمؤسسة على أنها " خزان للمعارف" لا كونها مركز للعقود أو نظام مفتوح فقط. لذلك نسعى من خلال هذا البحث إلى إبراز ماهية المقاربة الإدراكية للحوكمة و ما يميز عملية خلق القيمة في هذه المقاربة لكونها تختلف براديغميا عن ما هو متبنى في المقاربة التقليدية. ثم محاولة توضيح كيف يمكن للمسجد باعتباره مؤسسة دينية أن يستفيد من الحوكمة الإدراكية في خلق القيمة التي تسمح له بممارسة دوره الحقيقي. Although the participatory approach to governance is widely spread by dominating the "shareholderdriven" financial approach, the disciplinary paradigms that characterize the two contractual theories (agency theory, property rights theory, cost theory transactions), ignored the productive dynamics of the company, which favored the emergence of another paradigm allowing to construct a different conception of the organizational and administrative efficiency called the "cognitive approach of the governance" or "Cognitive governance", which is based on the creation of value through the promotion of skills, learning and creativity, especially in the knowledge-based economy where the enterprise is regarded as a "repertoire of knowledge" rather than a contract node or an open system only. Through this research, we try to highlight the cognitive approach of governance and deduce the characteristics of value creation because they differ radically from what is adopted in the traditional approach. Our main question revolves around the following question: What are the most important benefits of value creation in the cognitive approach to governance?
value creation as part of the cognitive approach to governance and its applicability to religious institutions
مقال
Keywords: المقاربة التعاقدية للحوكمة – المقاربة الإدراكية للحوكمة – خلق القيمة – اقتصاد المعرفة – المؤسسة الدينية